2021
DOI: 10.3390/ijerph18095033
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary Time, Physical Activity Levels and Physical Fitness in Adults with Intellectual Disabilities

Abstract: Purpose: This cross-sectional study assessed the associations of gender, age, level of intellectual disabilities (IDs) and of daily sedentary and physical activity (PA) time with physical fitness in adults with ID. Materials and methods: Sixty adults (mean age = 39.19 ± 11.70 years) with ID participated in this cross-sectional study. PA was monitored for 7 days using an ActiGraph GT3X monitor. Physical fitness was measured with a 6-min walking test, isometric push-up test, modified curl-up test, handgrip stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 57 publications
(89 reference statements)
0
17
0
Order By: Relevance
“…Studies in DI report the use of different dynamometers, among which the following stand out: hydraulic dynamometer (Jamar, Bolingbrook, IL, USA) [ 35 , 49 ]; (Takei, Tokyo, Japan) [ 48 , 50 , 51 ]; (MP 150, California, USA) [ 52 ]; (Baseline LiTE, New York, NY, USA) [ 14 ]. Other investigations do not declare the type of dynamometer used [ 53 , 54 , 55 ]. (b) The adjustment of the dynamometer grip.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in DI report the use of different dynamometers, among which the following stand out: hydraulic dynamometer (Jamar, Bolingbrook, IL, USA) [ 35 , 49 ]; (Takei, Tokyo, Japan) [ 48 , 50 , 51 ]; (MP 150, California, USA) [ 52 ]; (Baseline LiTE, New York, NY, USA) [ 14 ]. Other investigations do not declare the type of dynamometer used [ 53 , 54 , 55 ]. (b) The adjustment of the dynamometer grip.…”
Section: Discussionmentioning
confidence: 99%
“…The disability identification standards use IQ and adaptive behavior to identify ID and classify the levels of ID, which are consistent with the WHO and the American Association on Intellectual and Developmental Disability (AAIDD) classification criteria for ID. Participants must meet the following criteria to be eligible for the study: (a) aged 5–17 years, (b) previously diagnosed with significant limitations in intellectual functioning and adaptive behavior, (c) have no other physical disability or health condition that may limit musculoskeletal movements (e.g., cerebral palsy), (d) possess sufficient verbal communication skills to follow instructions and complete all the tests independently [ 32 ], without behavioral problems that may affect the performance of instructions (e.g., oppositional behavior) [ 24 ], (e) have completed the full TGMD-2 test program and had at least three days (two school days and one weekend day) of valid accelerometer data, and (f) be present during the investigation. According to the criteria, 49 students were excluded due to the following reasons: (a) 7 students had other physical disabilities or health conditions that limit musculoskeletal movements, (b) 12 students were unable to follow instructions to complete all tests of TGMD-2 independently, (c) 3 students had behavioral problems that interfered with the execution of instructions, (d) 23 students’ accelerometer data did not cover at least three valid days, and (e) 4 students withdrew during the test.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the findings from previous literature, university student participants often were unaware of PA programs or facilities on campus. Hsu et al (2021) found that nearly 70% of college students with disabilities reported that they used campus recreation facilities less than five times per semester and also nearly 40% of them have never used the facilities. This suggests a potential gap between awareness of opportunities and the existing programs on campus.…”
Section: Lack Of Awareness By Cusdmentioning
confidence: 99%